Multimedia Audio Visual Untuk Promosi Wisata Alam Puncak Aua Sarumpun Kabupaten Tanah Datar - Iskandar, Riki (Jurnal Sains Informatika Terapan, 2022)
Tourism is one of the most important things for a country. Indonesia is a country that has many tourist attractions to visit, both natural tourism and artificial tourism. Since it was developed in 2017, Aua Sarumpun tourist destination in Tanah Datar Regency continues to improve. This tourist attraction located at the height of Nagari III Koto Rambatan, offers charming and beautiful natural scenery. The peak of Aua Sarumpun is located in Jorong Situra nagari Tigo Koto District Rambatan Tanah Datar Regency. There are various facilities available in Aua Sarumpun such as camping area, Langkok Resort, food stalls, parking lots, weeds, Mushollah, tree houses, relaxing places that lead directly to Singkarak lake, public lavatories and flower gardens. In the tourist area of Aua Sarumpun there is also Langkok Resort which has facilities such as Mushollah, swimming pool, homestay, lesehan place, wahan flying fox, camping area and public lavatories. In the design of The Peak Aua Sarum tourism promotion media, the basic concept is to create a Promotional Media for the tour so that the number of tourists who visit Aua Sarumpun tourist attractions. Puncka Aua Sarumpun Promotional Media Design will be published in selected media for the needs and promotion of the tour.